A Study of Influence Distance and Road Safety Avoidance Distance from Postearthquake Building Debris Accumulation - Wei Wang; Nana Zhang; Leiming Wang; Ziyi Wang; Donghui Ma (Advances in Civil Engineering)
To study the influence of the debris accumulation caused by the continuous collapse of the postearthquake building structure on the avoidance distance of the road red line, taking the typical masonry structures of three stories, five stories, and seven stories as examples, this study simulates the process of sloughing collapse and the positive and negative collapse along the Z axis of the building structure under 28 different seismic conditions in details. Taking “the flying stones” into consideration, this study divides the influence distance of the collapsed building structure under earthquakes into (a) the safety distance during earthquakes and (b) the main influence distance of the debris accumulation after the earthquake. In this study, two types of movement laws of flying stones are analyzed statistically first. Then, the statistical analysis and hypothesis testing are carried out on the main influence distance of all the debris accumulation using the influence width coefficient, and the main influence distance distribution probability models of the debris accumulation of the collapsed building structure under earthquake excitation are established. The distribution models include the gamma distribution and the extreme value type III along the Z axis and the normal distribution probability model along the X axis. Finally, a simplified calculation table of the influence distance of collapsed building structures is established. It provides a scientific basis for the safe control distance of buildings to avoid the road red line and for the minimum distance between the buildings and people after a destructive earthquake.